130 Boerhaave's Syndrome: A Rare Complication of Cannabinoid-Induced Hyperemesis Syndrome. (4th May 2021) - Clarke, T
Abstract: A 22-year-old man was referred to our surgical department with severe central chest pain after a three-day history of > 200 episodes of vomiting a day on a known background of cannabinoid hyperemesis syndrome. A computed tomography (CT) scan showed a ruptured oesophagus and pneumomediastinum, in keeping with Boerhaave's syndrome. Conservative treatment with keeping the patient nil by mouth and administering intravenous fluids, anti-emetics and broad-spectrum antibiotics was initiated. Follow up CT showed significant reduction in pneumomediastinum. The patient was discharged home 7 days after admission. Spontaneous rupture of the oesophagus is a rare but potentially fatal event. It is caused by an abrupt rise in intra-luminal pressure, usually secondary to forceful vomiting. CT scan should be performed in all suspected cases as the findings dictate management, this being conservative, endoscopic, or surgical. We report on the first published case of Boerhaave's syndrome as a result of cannabinoid hyperemesis syndrome.